A Qualitative Analysis of WhatsApp Integration on Speaking Vocabulary Development - Khan, Raja Muhammad Ishtiaq; Alahmadi, Alaa; Radzuan , Noor Raha Mohd; Shahbaz, Muhammad (UIN Salatiga, 2024)
The use of mobile devices is common in the development of language learning, and it has remarkable effects on fostering language instruction. The present study is a qualitative attempt to determine the learners’ attitudes on integrating m-learning in developing the vocabulary of speaking performance. The study used a qualitative research method to attain the data. 25 EFL learners were the participants of the study. Semi-Structured interviews were used to gather the learners’ responses. The findings suggest that learners endorsed the m-learning app to develop vocabulary learning for speaking performance. More specifically, the analysis of the data exhibited that the use of WhatsApp deemed usleful in the retention of vocabualry for spoken proficiency.